Mosquito survey reveals the first record of Aedes (Diptera: Culicidae) species in urban area, Annaba district, Northeastern Algeria - Arroussi, J.E. R; Bouaziz, A; Boudjelida, H (My University, 2021)
The diversity, distribution and ecology of mosquitoes, especially arbovirus vectors are important indices for arthropod-borne diseases control. The mosquito larvae were collected in different habitats in four sites of Annaba district, Algeria, during the period of March 2018 to February 2019 and the properties of larval habitats were recorded for each site. The systematic study revealed the presence of 8 species belonging to 4 genera; including Culex pipiens (Linnaeus, 1758), Culex modestus (Ficalbi, 1889), Culex theileri (Theobald, 1903), Culiseta longiareolata (Macquart, 1838), Anopheles labranchiae (Falleroni, 1926), Anopheles claviger (Meigen, 1804), Aedes aegypti (Linnaeus, 1762) and Aedes albopictus (Skuse, 1894). Among the species, C. pipiens presented the highest species abundance (RA %) (55.23%) followed by C. longiareolata (20.21%). The Aedes species are recorded for the first time in the study urban area. Variation of diversity in different sites depends on the type of breeding habitat. These results provided important information on species diversity, distribution and factors associated with breeding habitats. They could be used for the mosquito control and to prevent the spread of mosquito-borne diseases to the population of the region.